CORK'EWS: From microstructural composition into macrostructural performance - Oliveira, M.J.; Rato, V. (Proceedings of the 2nd International Conference of Biodigital Architecture and Genetics, 2014)
The main goal of this research was to develop a new, adaptable and personalized cork industrial product for environmental performance applications. The project started with the standard insulation products from Amorim Insulation Industries. Inspired on natural growth and performance, it found its basis on the observation of the properties and composition of natural cork, and explored cork anisotropy in a digital form-finding process to design and fabricate. A full scale prototype was designed and produced by a personalized parametric definition, using the form-finding processes based on cork anisotropy to program the physical matter and the digital fabrication for an improved acoustical behavior. The results obtained contribute to an increasing and more diverse offer of expanded cork products, within the scope of the natural and sustainable products of Amorim Insulation Industries.